Legal Analysis Of Incident Reporting Against The Patient Safety Management System In Hospitals - Mukhammad Iqbal Pradana Pradana (Universitas Muhammadiyah Enrekang, 2024)
Patient safety in hospitals is still a major issue, with a wide range of services that have risks that threaten patient safety. Patient safety incidents (PSEs) are unintentional events and conditions that result in or have the potential to result in preventable harm to patients. According to the Minister of Health Regulation No. 11 of 2017, patient safety is a system that makes patient care safer, including risk assessment, identification and management of patient risks, incident reporting and analysis, the ability to learn from incidents and their follow-up, and the implementation of solutions to minimize the incidence of risk and prevent injury caused by errors due to carrying out an action or not taking action that should be taken. 2014, includes fear of being blamed, lack of commitment from management and related units, no reward from the hospital if reporting, not knowing which boundaries or what to report, and ineffective socialization of patient safety incidents. Therefore, hospitals must increase the awareness and ability of health human resources in analyzing, handling, and reporting patient safety incidents. Thus, patient safety incident reporting in hospitals is essential to improve patient safety. Hospitals must ensure that the patient safety incident reporting system is carried out effectively and efficiently.